Preconceptional, Gestational, and Lactational Exposure to an Unconventional Oil and Gas Chemical Mixture Alters Energy Expenditure in Adult Female Mice - Balise, Victoria D.; Cornelius-Green, Jennifer N.; Kassotis, Christopher D.; Rector, R. Scott; Thyfault, John P.; Nagel, Susan C. (Frontiers in Endocrinology, 2019)
Previous studies conducted in our laboratory have found altered adult health outcomes in animals with prenatal exposure to environmentally relevant levels of unconventional oil and gas (UOG) chemicals with endocrine-disrupting activity. This study aimed to examine potential metabolic health outcomes following a preconception, prenatal and postnatal exposure to a mixture of 23 UOG chemicals. Prior to mating and from gestation day 1 to postnatal day 21, C57BL/6J mice were developmentally exposed to a laboratory-created mixture of 23 UOG chemicals in maternal drinking water. Body composition, spontaneous activity, energy expenditure, and glucose tolerance were evaluated in 7-month-old female offspring. Neither body weight nor body composition differed in 7-month female mice. However, females exposed to 1.5 and 150 µg/kg/day UOG mix had lower total and resting energy expenditure within the dark cycle. In the light cycle, the 1500 µg//kg/day group had lower total energy expenditure and the 1.5 µg/kg/day group had lower resting energy expenditure. Females exposed to the 150 µg/kg/day group had lower spontaneous activity in the dark cycle, and females exposed to the 1500 µg/kg/day group had lower activity in the light cycle. This study reports for the first time that developmental exposure to a mixture of 23 UOG chemicals alters energy expenditure and spontaneous activity in adult female mice.